Analisis Perputaran Modal Kerja Pada UD. Karya Cipta Mandiri Kabupaten Toraja Utara - Lusdani, Westerini; Pundissing, Rati; Pagiu, Chrismesi (UKI Toraja Press, 2022)
The purpose of this study was to analyze working capital turnover at UD during the 2018-2020 period. Karya Cipta Mandiri, North Toraja Regency. This type of research is qualitative. Data obtained by conducting interviews, observation and documentation. The data analysis technique used is working capital analysis and working capital turnover. The results of this study indicate that in 2018, the working capital turnover rate was 34.60 times. In 2019, the working capital turnover rate increased by 35.32 times. In 2020, the working capital turnover rate decreased by 32.13 times, due to the covid-19 pandemic that hit the whole world.